Prevalence of Hepatitis C Virus and HIV among Libyans and Expatriates (Foreigners) in the City of Zawia, Libya - Asmahan Alfard; Fawzia Kahbar; Himedah Fheel Alboom; Najat Mansour; Mabroukah Khalleefah (AlQalam Journal of Medical and Applied Sciences, 2025)
Libya has the longest coastline in the Mediterranean basin, which increases the risk of the spread of hepatitis C virus and AIDS. This is a public health problem that affects most of the world’s population, including Libya, as the hepatitis C virus is considered the leading cause of cirrhosis and liver cancer worldwide. HIV/AIDS is a disease that puts the infected person at risk and therefore death. Liver cancer is not the most common cause of death, but it is the second most common cause of death worldwide. Therefore, the study aimed to determine the prevalence of hepatitis C and HIV among Libyans and foreigners arriving in Libya. The study was conducted in 2023 on Libyans and expatriates (foreigners) in the city of Zawia in the reference laboratory. Samples were collected, then 5 ml of the patient’s blood was taken and placed in a centrifuge to separate the serum, and 50 microns of it were transferred to the test strip using the RABID method. ELISA was also used. The modes of transmission of the hepatitis C virus and human immunodeficiency virus (AIDS) are blood and drug use. The prevalence rate of hepatitis C virus among Libyans was 0.016%, and among men it was 51.21% higher than among women. The age group of 21 to 30 years was also the most prevalent. The prevalence rate of HIV was 0.04%, and among men, it was 63.63%. The age group of 31 to 40 years was the most prevalent, with a higher prevalence rate than among women. As for Libyans who underwent the test for a specific purpose, the majority of them did so because of marriage, a rate of 56.09%. Among expatriates (foreigners), the prevalence rate of hepatitis C was 0.05%. Its rate among men was higher than among women, at 86.66%. The age group of 21 to 30 years was the most prevalent. As for HIV, it was 0.06%, and in the age group of 10 to 20 years, its rate among men was 100%. Most of the samples were among expatriates, most of them for treatment purposes, at 53.33%. Regarding people infected with the hepatitis C virus from different countries, the majority of those infected came from Egypt, 60%, while those infected with HIV came from Nigeria, 50%. The hepatitis C virus is a serious disease that is transmitted through blood. As arrivals from most African countries or other countries are high, it is because the region is known for the spread of hepatitis C virus. The study showed that the prevalence of the hepatitis C is 0.50%, and the incidence of HIV/AIDS is 0.06%, both among men. تتمتع ليبيا بأطول خط ساحلي في حوض البحر الأبيض المتوسط، مما يزيد من خطر انتشار فيروس التهاب الكبد الوبائي والإيدز. وهذه مشكلة صحية عامة تؤثر على معظم سكان العالم، بما في ذلك ليبيا، حيث يعتبر فيروس التهاب الكبد C السبب الرئيسي لتليف الكبد وسرطان الكبد في جميع أنحاء العالم. فيروس نقص المناعة البشرية/الإيدز هو مرض يعرض الشخص المصاب للخطر وبالتالي الموت. سرطان الكبد ليس السبب الأكثر شيوعا للوفاة، ولكنه ثاني أكثر سبب للوفاة شيوعا في جميع أنحاء العالم. ولذلك هدفت الدراسة إلى تحديد مدى انتشار التهاب الكبد الوبائي وفيروس نقص المناعة البشرية بين الليبيين والأجانب الوافدين إلى ليبيا. أجريت الدراسة عام 2023 على الليبيين والمغتربين (الأجانب) في مدينة الزاوية في المختبر المرجعي. تم جمع العينات، ثم أخذ 5 مل من دم المريض ووضعها في جهاز الطرد المركزي لفصل المصل، ونقل 50 ميكرون منه إلى شريط الاختبار بطريقة RABID. تم استخدام ELISA أيضًا. طرق انتقال فيروس التهاب الكبد C وفيروس نقص المناعة البشرية (الإيدز) هي تعاطي الدم والمخدرات. بلغ معدل انتشار فيروس التهاب الكبد C بين الليبيين 0.016%، وبين الرجال أعلى منه بين النساء بنسبة 51.21%. وكانت الفئة العمرية من 21 إلى 30 عامًا هي الأكثر انتشارًا أيضًا. وبلغت نسبة انتشار فيروس نقص المناعة البشرية 0.04%، وبين الرجال 63.63%. وكانت الفئة العمرية من 31 إلى 40 سنة هي الأكثر انتشارا، مع معدل انتشار أعلى منه بين النساء. أما الليبيون الذين خضعوا للاختبار لغرض محدد، فإن غالبيتهم فعلوا ذلك بسبب الزواج بنسبة 56.09%. أما بين الوافدين (الأجانب)، فقد بلغت نسبة انتشار التهاب الكبد الوبائي (سي) 0.05%. وكانت نسبته بين الرجال أعلى منها بين النساء حيث بلغت 86.66%. وكانت الفئة العمرية من 21 إلى 30 سنة هي الأكثر انتشارا. أما فيروس نقص المناعة البشرية فقد بلغت 0.06%، وفي الفئة العمرية من 10 إلى 20 سنة بلغت نسبته بين الرجال 100%. وكانت معظم العينات من الوافدين، وأغلبها لأغراض العلاج، بنسبة 53.33%. وفيما يتعلق بالمصابين بفيروس التهاب الكبد الوبائي سي من دول مختلفة، فإن غالبية المصابين جاءوا من مصر بنسبة 60%، بينما جاء المصابون بفيروس نقص المناعة البشرية من نيجيريا بنسبة 50%. فيروس التهاب الكبد C هو مرض خطير ينتقل عن طريق الدم. نظرًا لأن عدد الوافدين من معظم البلدان الأفريقية أو البلدان الأخرى مرتفع، فذلك لأن المنطقة معروفة بانتشار فيروس التهاب الكبد الوبائي. وأظهرت الدراسة أن نسبة انتشار التهاب الكبد الوبائي سي تبلغ 0.50%، ونسبة الإصابة بفيروس نقص المناعة البشرية/الإيدز 0.06%، سواء بين الرجال